2016
DOI: 10.48550/arxiv.1603.03349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personalized Persuasion for Social Interactions in Nursing Homes

Abstract: This paper presents our preliminary investigation and approach towards a mixed physical-virtual technology for stimulating social interactions among and with older adults in nursing homes. We report on set of surveys, apps and focus groups aiming at understanding the different motivations and obstacles in promoting social interactions in institutionalised care. We then present our approach to address some of the key themes found, e.g., the technological disparity, lack of conversation topics and opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In our previous work [8] we reported on the results from surveys and visits to nursing homes. We identified that i) friendships in nursing homes are difficult, especially in the transition period, and that ii) contact is rather infrequent between older adults and their relatives, especially younger adults, often due to the lack of common topics of conversation and the lack of time.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [8] we reported on the results from surveys and visits to nursing homes. We identified that i) friendships in nursing homes are difficult, especially in the transition period, and that ii) contact is rather infrequent between older adults and their relatives, especially younger adults, often due to the lack of common topics of conversation and the lack of time.…”
Section: Introductionmentioning
confidence: 99%